PERANCANGAN APLIKASI RENCANA ANGGARAN BIAYA (RAB) PEMBANGUNAN KAPAL PERIKANAN (STUDI KASUS GALANGAN KAPAL DI BAGAN SIAPI-API) - Wandy Leo Pandiangan; Ronald Mangasi Hutauruk; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
In general a boat building must be adjusted with cost estimation, to creates efficient and effective building. Cost estimation is an importance activity on boat building because it will be a starting point to make offering finance system and scheduling implementation. Nowaday, the traditional shipyard at Bagansiapi-api still using building cost calculation manually, where as it is need long process and more complex. This research aim is to create RAB aplication for traditional shipyard’s boat building at Bagan Siapi-api, where it is constructed by using Visual Basic for Applications (VBA) or Macro Excel. Data of costs of material as well as wedge are collected and programmed to be a syntax to create user interface for the ship with principal dimensions as LOA = 14 m, B = 3,2 m, d = 1,10 m. Building cost consist of hull and bridge, machinery and equipment, electrical, navigation equipment, additional equipment, shipyard services, purse seine fishing gear, sea trial that each price are estimated based on interview to ship owner and foreman. The result of RAB is Rp605.699.000,- . This aplication also can simplify calculation process for every users.Keywords: Bagan Siapi-api, Cost Estimation, Macro Excel, Purse Seine, Shipyard